Comparison between cloud sim and green cloud in measuring energy consumption in a cloud environment - Atiewi S.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cloud computing is a model that relies on sharing computing resources rather than having local servers or personal devices to handle applications. Numerous studies have shown that by replacing traditional computing with cloud infrastructure, the total power consumption can be decreased because cloud computing power consumption is influenced by four key cloud factors: dynamic provisioning, multi-tenancy, server utilization, and data center efficiency. Considering the huge amount of energy consumed by computing equipment in the last several years, energy consumption and sustainability have become one of the main areas of research. Thus, obtaining high performance at a reduced cost in cloud environments has reached a turning point where computing power is no longer the most important concern. Calculate the amount of energy consumption in a real cloud computing infrastructure is difficult. Thus, simulation tools have been developed in recent years to enable cloud computing researchers to analyze a cloud computing environment. This paper will introduce and compare the two popular cloud simulators: Cloud Sim and Green Cloud. Both simulators provide scenarios for cloud computing based on utilization, virtualization, and load and energy consumption of the server. The comparison showed that the Green Cloud simulator is more advantageous than the Cloud Sim simulator based on an accurate measurement of energy consumption in a cloud computing environment. © 2014 IEEE.